TBM 700 Trestle Design as Supporting Equipment for the Aircraft Maintenance Care and Practice of Cadets - Rafie Ahza Ismulyono, Yudistira; Dwi Cahyo, Bayu (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
One of the supporting tools for Socata TBM 700 aircraft maintenance is the trestle, this tool is responsible for helping various aircraft checking processes such as jacking, leveling, and lifting. As a supporting tool, the hangar of the Politeknik Penerbangan Surabaya already has these tools. More specifically, the tool available is a hydraulic jack. This tool has the primary function of supporting the jacking process. However, the jacking tool owned by the Politeknik Penerbangan Surabaya is considered less effective and efficient in operation and safety, so creating a new tool with a more qualified level of efficiency and effectiveness is necessary. The new variant of the supporting tool is called the C17 trestle. The method used in this work is an experimental method that starts by designing a tool from a bottle Jack made from high-carbon steel. The primary purpose of this study is to determine the efficiency of the C17 trestle time working and safety during the maintenance process and practice by cadets. The results of this study show that the C17 trestle can be operated manually by a minimum of two people with an average time of 2 minutes 32 seconds and increases the percentage of work security and safety when the tool is used. This shows that the C17 trestle design is more suitable for use during the jacking process on the Socata TBM 700 aircraft